Kewajipan Nazar (Penaakulan) dan Keharaman Taklid di Sisi Muhammad Bin Yusuf al-Sanusi Menerusi Karyanya Sharh al-ʻAqidah al-Kubra: The Obligation of Nazar (Reasoning) and the Prohibition of Taqlid according to Muhammad Bin Yusuf al-Sanusi through His Work Sharh al-ʻAqidah al-Kubra - Mohamad Darwi, Mohd Firdaus; Khairuddin, Wan Haslan; Mahmood, Abdull Rahman (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This article discusses the obligation of nazar and the prohibition of taqlid according to Muhammad bin Yusuf al-Sanusi through his work Sharh al-ʻAqidah al-Kubra. The main issues highlighted are: [i] evidence and argumentation of the obligation of nazar on the side of al-Sanusi; [ii] al-Sanusi’s response to those who deny nazar; and [iii] the law of taqlid faith on the part of al-Sanusi. The writing of this article is based on a qualitative study using the content analysis method of al-Sanusi’s work entitled Sharh al-ʻAqidah al-Kubra. In addition, his other works and the works of other scholars related to the discussion are also seen to strengthen the analysis. The Qur’an’s repeated affirmation of nazar makes it a separate obligation separate from the obligation of maʻrifatullah even though the two are closely related. Iman taqlid that is empty of nazar shows the defect of maʻrifatullah. Therefore, al-Sanusi is very strict in the law of taqlid in order to guarantee the safety of the mukallaf in this world and the hereafter.